Spatial harvest scheduling for oak coppices conversion into high forest involving wood production management - Caglayan, İnci and Yeşil, Ahmet Yeşil and Zengin, Hayati and Engin Ünal, Murat (Bosque (Valdivia), 2018)
Oak forests in northern Turkey have been largely managed as coppice. Nevertheless, in parallel with the decrease in demand of firewood and charcoal, the coppices, having no social demand or regional pressure, have been converted into high forests since 2006. Because of this new regulation, a potential need has arisen to schedule forest harvests activities, which is based on the natural regeneration in those forests. The objective of this research was to develop a spatial forest planning process to schedule new harvests activities in coppices conversion into high forests. In the proposed study, four different planning strategies were used to estimate the most appropriate period for regeneration. Constraints essentially included those related to the need for an even flow, adjacency and to adhere to a maximum opening size. The scheduling process employed a mixed integer linear programming to schedule harvest activities and to maximize amount of harvested volume in planning horizon. The process was employed for the development of 100-year planning horizon for a Sergen forest range in the Thrace region of northern Turkey that was 3,448.8 ha in size. For obtaining various spatial data and solving the mathematical model, ArcMap and GAMS programs were used, respectively. Results showed that the value of the objective function in the case study forests could significantly increase when there is no constraint under the proposed harvesting plans in strategy 1 (3,652,072.8 m³). The amounts of wood production were similar in strategy 2 (3,547,613.5 m³) and strategy 4 (3,547,393.5 m³).